Epidemiology of Gallbladder Cancer in Saudi Arabia - Alqahtani, Saleh A (Cancer Manag Res, 2020)
BACKGROUND: Gallbladder cancer is generally rare but can be more common in some populations. The aim of this study was to present an analysis of gallbladder cancer epidemiology in Saudi Arabia. MATERIALS AND METHODS: A retrospective study of gallbladder cancer cases in Saudi Arabia from 2004 to 2015 was conducted. The gallbladder cancer data were accessed through the Saudi Cancer Registry (SCR) reports for 13 administrative regions. The number of gallbladder cancer cases with percentage, the crude incidence rate (CIR) and the age-standardised incidence rate (ASIR), stratified by regions, gender, and the years of diagnoses were analysed. RESULTS: A total of 1678 gallbladder cancer cases, 702 in males and 976 in females, were registered between 2004 and 2015. Saudi women and men in the 75 and above age-group were found to have the highest diagnosis rate of gallbladder cancer. In males, the overall ASIR among Saudi males was 1.1 per 100,000 (95% CI, 0.9 to 1.2). The Eastern region had the highest overall ASIR at 1.5 per 100,000 males, followed by Tabuk and Riyadh at 1.4 and 1.3 higher than other regions (F(12,143)=1.930, P<0.001). The overall ASIR among Saudi females was 1.6 per 100,000 (95% CI, 1.4 to 1.7). Riyadh had the highest overall ASIR at 2.4 per 100,000 females, followed by the Eastern region, and Qassim at 1.9 and 1.5, respectively, all higher than other provinces of the country (F(12,143)=2.496, P<0.005). The ASIR and CIR were lower among males than females (ratio 0.7). CONCLUSION: Gallbladder cancer incidence is relatively low in Saudi Arabia. The rates were higher in females than males. ASIR showed variations between different provinces of Saudi Arabia. In females, the highest ASIR was in Riyadh. In males, ASIR was highest in the Eastern region of Saudi Arabia.